HLA-A*02:07 Is a Protective Allele for EBV Negative and a Susceptibility Allele for EBV Positive Classical Hodgkin Lymphoma in China - Huang, Xin (Public Library of Science, 2012)
HLA-A2 protects from EBV+ classical Hodgkin lymphoma (cHL) in Western Europe, but it is unknown whether this protective effect also exists in the Chinese population. We investigated the association of HLA-A2 and specific common and well documented HLA-A2 subtypes with EBV stratified cHL patients (n = 161) from the northern part of China. Quantitative-PCR and sequence-based subtyping was performed to identify HLA-A2 positive samples and their subtypes. 67 (42%) of the cHL patients were EBV+. There were no significant differences in percentages of HLA-A2 positivity between cHL and controls (65% vs 66%) and between EBV+ and EBV− cHL patients (70% vs 61%). The frequency distribution of HLA-A2 subtypes was significantly different between EBV stratified cHL subgroups and controls. This difference was most striking for the HLA-A*02:07 type with a frequency of 38% in EBV+ cHL, 8% in EBV− cHL and 20% in controls. Significant differences were also observed for the HLA-A*02:07, HLA-A2 (non-02:07) and the A2-negative typings between EBV+ cHL vs controls (p = 0.028), EBV− cHL vs controls (p = 0.045) and EBV+ vs EBV− cHL cases (p = 2×10(−5)). In conclusion, HLA-A*02:07 is a predisposing allele for EBV+ cHL and a protective allele for EBV− cHL in the northern Chinese population.